Evaluation of Student Mental Workload in Multicampus Lectures of Cirebon Industrial Engineering Block System - Muslim, Yudisiasita; Widyanti, Ari (Journal of Research in Industrial Engineering and Management, 2024)
The object of this research is the Industrial Engineering (IE) study program at Bandung Institute of Technology Cirebon Campus which runs block and non-block system lecture. The block system is a lecture by combining two to three class meeting of a course in one day while non-block system is a one time meeting in a week. Block system faced a lot of complained from students because the class were too hectic, the inability of students to receive a lot of quantitative material, and the monotony of the class. This study evaluates student’s mental workload by comparing the results of experimental measurements while attending block and non-block classes. Mental workload was measured with three measuring instruments, named NASA-TLX, Karolinska Sleepiness Scale (KSS), and Stroop test. Experimental results with 38 students concluded that there is actually no significant difference in mental workload between the two systems. Factors that could cause this results to happen include previous experience in block classes, non-optimal block system instructional learning time, mental fatigue in students, and decreased attention.